Silver/Copper Nanoparticle-Modified Polymer Chitosan/PVA Blend Fibers - Dikeledi S. More; Makwena J. Moloto; Nosipho Moloto; Kgabo P. Matabola (International Journal of Polymer Science)
In this study, chitosan (CS)/poly(vinyl alcohol) (PVA) (CS/PVA) blend nanofibers with varying weight ratios and silver (Ag)/copper (Cu)/CS/PVA composite fibers have been prepared successfully by the electrospinning process. The tip-to-collector distance was kept at 15 cm, and the applied voltage was varied from 15 to 25 kV. The effects of the weight ratios and applied voltage on the morphology and diameter of the fibers were investigated. The resultant fibers were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The SEM results showed that increasing the amount of chitosan in the CS/PVA blend resulted in a decrease in the fiber diameter from 162 to 89 nm while an increase in the voltage from 15 to 25 kV led to a decrease in the fiber diameters. Furthermore, the SEM results indicated that an increase in the fiber diameter from 161 to 257 nm was observed while morphological changes were also observed upon the Ag/Cu addition. The latter changes are perceived to be a result of increased conductivity and higher charge density.